Efeitos da alimentação/digestão e do jejum prolongado sobre a função cardíaca de cascavéis, Crotalus durissus terrificus - Paula, Gabrielle Silveira de (2012)
Some snakes have the ability to survive long periods without food and are capable to ingest large meal size. The ingestion of proportionally large preys triggers an expressive increase on the oxidative metabolic demand (SDA Specific Dinamic Action) which can become several times higher than the resting metabolic rate. The two described extreme situations might lead to cardiac changes to adapt structure and function in order to afford these two opposite physiological demands. During long food deprivation (Phase III), the depletion of the body structure may affect the heart muscle. That should be reverted to the SDA and prevent an overload on cardiovascular system. The standard cardiac function of South-american Rattlesnake, Crotalus durissus terrificus, was described as well as the changes caused by long term food deprivation and SDA. The importance of sodium-calcium exchanger (NCX), functionality of sarcoplasmic reticulum, extracellular calcium dependence and the effect of adrenergic stimulation were tested in adult animals at 30°C, under three different metabolic states: postabsorptive, SDA peak and food deprivation. The ventricular mass does not change after food deprivation and SDA. The force of contraction was higher in the base of the heart if compared to the apex, but there is no difference among the experimental groups and it is probably reflex of the fiber orientation in each region of the ventricle. The sarcoplasmatic reticulum is functional in all groups, but the dependence of reticular calcium is lower during starvation compared to the other groups. Muscle contraction is mostly supported by the extracellular Ca2+. The NCX have minor contribution to force generation (20%) but has a major role pumping calcium out of the cell (faster than SERCA). The increase in extracellular Ca2+ concentration during digestion can augment twitch force and would represent a contractile advantage to support the increased cardiac work without the development of hypertrophy. The adrenergic stimulation produced sustained increase in Fc for a wide range of stimulation frequencies in all the tested groups.